2020
DOI: 10.2337/dc20-0682
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is a Risk Factor for Greater COVID-19 Severity

Abstract: The coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has attracted increasing worldwide attention (1). Obesity commonly aggravates the severity of respiratory diseases, but it is currently not known whether obese patients are also more likely to have greater COVID-19 severity of illness. We investigated the association between obesity and COVID-19 severity of illness among patients with laboratoryconfirmed SARS-CoV-2 infection. We enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
356
3
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(397 citation statements)
references
References 3 publications
23
356
3
15
Order By: Relevance
“…According to the previous investigations, older age has been nominated as an important risk factor for mortality in SARS and Middle East respiratory syndrome (MERS) [33,34]. Consistent with our observation, studies on COVID-19 have also reported that the increase in age was associated with a high mortality rate [15,36].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to the previous investigations, older age has been nominated as an important risk factor for mortality in SARS and Middle East respiratory syndrome (MERS) [33,34]. Consistent with our observation, studies on COVID-19 have also reported that the increase in age was associated with a high mortality rate [15,36].…”
Section: Discussionsupporting
confidence: 90%
“…To date, the exact mechanisms underlying strong association between obesity and COVID-19 severity were not clari ed. However, it may be the consequence of low-grade chronic in ammation and suppressed immunity in obese persons [33].…”
Section: Discussionmentioning
confidence: 99%
“…Age, comorbidities, c-reactive protein, albumin, cytokine, lactate dehydrogenase, D-dimer, albumin, platelet, lymphocyte, neutrophil, smoking, cough, expectoration, chest pain, dyspnea, CT manifestations, et al, have been reported to be associated with the severity of COVID-19 in some small studies in China, [15][16][17][18][19][20][21] and other countires. 13,22,23 Jiangsu, a province in China over 600 km from Hubei without common geographical borders and 80 million population, reported over 600 patients infected with COVID-19.…”
mentioning
confidence: 99%
“…These are all important risk factors for cardiovascular disease, which is one of the leading causes of morbidity worldwide and is anticipated to rise substantially over the next decades [6,7]. On admission, 20-51% of COVID-19 patients reported at least one comorbidity, with the most common being diabetes (10-20%), hypertension (10-15%) and other cardiovascular metabolic comorbidities(7-40%) [8][9][10][11][12][13]. A retrospective multicenter study conducted in China revealed that patients with these comorbidities (based on self-report) on admission experienced poorer clinical outcomes than those without comorbidities [8].…”
Section: Introductionmentioning
confidence: 99%